Implementation and Effectiveness of Sustainable Cooperative Management Practices - Attolba-Aquino, Ruth Ann Marie; Castañeda, Marc Oliver (Journal of Interdisciplinary Perspectives, 2025)
This study examined the implementation and effectiveness of sustainable cooperative management practices, focusing on the core management functions: planning, organizing, directing, and controlling. Guided by the Resource-Based View Theory, Sustainable Development Theory, Fayol’s Principles of Management, and Stakeholder Theory, the study addressed a research gap: limited literature on the operational and managerial strategies that drive cooperative sustainability at the local level. A descriptive-quantitative design was utilized, surveying 201 cooperative managers and board members selected through simple random sampling. Statistical analyses, including medians and Spearman’s rho correlation, were applied. Findings revealed that management practices were highly implemented across all functions. Planning (Mdn = 3.95) was strong in strategic and financial planning but weaker in market research (Mdn = 3.44). Organizing showed robust governance (Mdn = 3.90) but moderate technological integration (Mdn = 3.35). Directing emphasized leadership and communication (Mdn = 4.01), while feedback mechanisms were less developed. Controlling was highly implemented in financial monitoring (Mdn = 4.04) but needed stronger performance evaluation systems (Mdn = 3.50). Effectiveness ratings were Highly Effective in the social (Mdn = 4.11) and economic (Mdn = 3.80) aspects, and Very Highly Effective in the environmental aspect (Mdn = 4.22). Strong and statistically significant correlations (ρ = 0.511–0.736, p < 0.05) were found between the implementation of management practices and sustainability outcomes. Key challenges included limited financial and human resources (Mdn = 3.54) and underdeveloped performance assessment systems. A sustainability framework was proposed to address these gaps, emphasizing strategic planning, technological integration, and strengthened monitoring. The study offers practical implications for cooperative leaders, stakeholders, and policymakers in enhancing sustainable management practices and achieving long-term resilience.